Hofstede’s Cultural Model, LMX and Pakistani Historic-socio-political Discourse: An Analytical Critique - Dr. Naveed Yazdani (Journal of Islamic Thought and Civilization, 2013)
This paper grounds its analytical historical discourse of Pakistani culture, society and leadership (political, social and economic) in Hofstede’s model of national and organizational culture. It borrows from LMX theory of leadership which entails both transactional and transformational elements and applies it in the context of Pakistani leadership style. Since the founding ideology of Pakistan is the religion of Islam, the paper also undertakes a detailed account of Divine Commands based socio-economic Islamic precepts. It also presents some empirical evidence reflecting the present Pakistani cultural and societal values embedding both the culture and leadership style of the country. The paper challenges Hofstede’s labeling of Pakistani culture as collectivistic and calls for future research on the ‘Dark Side’ of LMX practices prevalent in Pakistani discourse.